Application of GeO2 nanoparticle as electrically erasable memory and its photo catalytic behaviour. (6th June 2018) - Seal, M; Bose, N; Mukherjee, S
Abstract: Germanium oxide nanoparticle is synthesized from bulk GeO2 powder through hydrothermal technique. The structural characterization of the prepared sample is performed with x-ray Diffraction and Transmission Electron Microscope. From the PL emission spectra and x-ray photoelectron spectra, the existence of oxygen defects inside the sample is confirmed. Thermogravimetric (TG) analysis of the sample shows that there is no weight loss with increase in temperature instead of a very little weight gain. An estimation of Oxygen vacancy concentration is made from the amount of weight gain as measured during TG analysis. The sample is also characterized with PE loop tracer, which indicates that GeO2 nanoparticle is able to show hysteresis loop regarding variation of Polarization with electric field. Such phenomenon implies that the sample can be used as electrically erasable memory device. Further, GeO2 nanoparticle is also exploited as photo catalyst to degrade Methylene Blue (MB) solution in the presence of ultraviolet ray. This phenomenon is also explained with oxygen vacancy.